Tanzania Diagnostic Review of Consumer Protection and Financial Literacy : Volume 2. Comparison with Good Practices - World Bank Group (World Bank, Washington, DC, 2017)
In 2011, only 17.3 percemt of adults in Tanzania had an account at a formal financial institution and 56 percemt did not have any access to financial services. Most of the population lives in rural areas with very low incomes and poor infrastructure, and women are especially disadvantaged. Such limited access to formal financial services also inhibits financial literacy – awareness of benefits and risks, and how to take advantage of opportunities. Despite significant challenges, all institutional elements of the formal financial sector in Tanzania are in place, helping its gradual expansion, and in some segments technology is driving rapid growth – particularly in mobile and electronic payments. Still, gaps and weaknesses in financial consumer protection and financial education remain some of the main obstacles to sustainability and greater trust in the financial sector. This Diagnostic Review was requested by the Ministry of Finance of Tanzania in November 2012. It provides a detailed assessment of Tanzania’s institutional, legal and regulatory framework against the World Bank’s Good Practices for Financial Consumer Protection. Three segments of the financial sector have been analyzed: banking, microfinance, and pensions. Insurance and securities segments will be considered at a later stage. Volume I of the Review summarizes the key findings and recommendations and Volume II presents a detailed assessment of each financial segment compared to the Good Practices.